A Literary Review of Kamala with Special reference to Jaundice - Kumar, Manish (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: In human beings Rakta dhatu is given utmost importance as the diseases pertaining to Rakta is more in incidence. Kamala issuch a disease where in the Rakta dhatu is vitiated primarily by Pitta dosha. Indulgences with pittaprakopaka nidana independently or after pitta pradhana vyadhis such as Pandu are considered as nidana for Kamala. Based on samprapti, it is manifested in two forms, Kostha Shaka Ashrita Kamala and Shaka Ashrita Kamala. Clinically they were mainly characterized by Haridra Netra, Twak, Nakha, Mootra and differentiated by Shweta varcha and Raktapeeta varcha respectively. Objective: - To understand the concept of the Kamala w.s.r Jaundice. Material & method-Data collected from various ayurvedic & modern textbook like Charak Samhita with Ayurved Dipika Commentary, Sushruta Samhita with Nibandhsangraha commentary, Ashtang Hriday with commentaries Sarvangasundara, Relevant articles published in various national and internationaljournals, Discussion: - In Ayurvedic literature kamala is described as pittaj nantmaja and raktapradoshaj vyadhi. The aggravated pitta dosh impairs the blood and tissue of the liver and blocksthe channelsof the liver. Thus, pitta isthrown back into blood leading to discoloration of eyes and skin. Conclusion: - The Kamala would be point out to a disease condition in which hunger and appetitefor food are diminished.